2003
DOI: 10.1016/s0002-9440(10)63610-3
|View full text |Cite
|
Sign up to set email alerts
|

MKK3 Mitogen-Activated Protein Kinase Pathway Mediates Carbon Monoxide-Induced Protection Against Oxidant-Induced Lung Injury

Abstract: The stress-inducible gene heme oxygenase (HO-1) has previously been shown to provide cytoprotection against oxidative stress. The mechanism(s) by which HO-1 provides this cytoprotection is poorly understood. We demonstrate here that carbon monoxide (CO), a byproduct released during the degradation of heme by HO, plays a major role in mediating the cytoprotection against oxidant-induced lung injury. We show in vitro that CO protects cultured epithelial cells from hyperoxic damage. By using dominant negative mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
166
2
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(174 citation statements)
references
References 29 publications
4
166
2
2
Order By: Relevance
“…LPS and ventilation both induced activation of AP-1 and NF-B ( Figures 6A and 6B); however, CO treatment did not modulate the activation of AP-1-or NF-B-binding activity compared with ventilation or LPS/ventilation treatment. Another intracellular pathway that is activated in lung injury is p38 mitogen-activated protein kinase (MAPK) (23). In our model LPS and ventilation increased activation of p38 MAPK; CO significantly increased p38 MAPK activation when compared with ventilation and LPS (Figure 7).…”
Section: Mechanisms Of Co-induced Antiinflammatory Effectsmentioning
confidence: 79%
“…LPS and ventilation both induced activation of AP-1 and NF-B ( Figures 6A and 6B); however, CO treatment did not modulate the activation of AP-1-or NF-B-binding activity compared with ventilation or LPS/ventilation treatment. Another intracellular pathway that is activated in lung injury is p38 mitogen-activated protein kinase (MAPK) (23). In our model LPS and ventilation increased activation of p38 MAPK; CO significantly increased p38 MAPK activation when compared with ventilation and LPS (Figure 7).…”
Section: Mechanisms Of Co-induced Antiinflammatory Effectsmentioning
confidence: 79%
“…Some of the potential candidates include Fas, p53, caspases, Bcl-2 family members, cytokines (IL-6, IL-11, IL-1β and TNF-α), growth factors (Vascular endothelial growth factor (VEGF), insulin-like growth factor (IGF) and keratinocytes growth factor (KGF)), heme oxygenase 1 (HO-1), and Toll-like receptor 4 (TLR4) [56,57,63]. First, exposure to hyperoxia induces an altered expression of many of Bcl-2 family members, including both proapoptotic (Bax, Bad, Bak) and antiapoptotic (Bcl-k L, Bclw, Bfl-1 and Bcl-2).…”
Section: Expression Of Regulatory Genes In Hyperoxic Cell Deathmentioning
confidence: 99%
“…Carbon monoxide (CO), a byproduct of HO degradation of heme, protects epithelial cells from hyperoxic damage. Using dominant negative mutants and mice deficient in different MAPKs, Otterbein et al demonstrated the cytoprotective effects of CO is mediated by specific MKK3/p38β pathways [57]. TLR4, a principal receptor for bacterial lipopolysaccharides (LPS), can be activated by noninfectious stimuli including hyperoxia [63].…”
Section: Expression Of Regulatory Genes In Hyperoxic Cell Deathmentioning
confidence: 99%
“…The CO exposed animals also had improved gastrointestinal transit and no animal deaths after the operation, compared to a survival of 58 % for the nonexposed rats (Nakao et al, 2003). In a model of acute lung injury in mice, CO showed cytoprotective effects and an attenuation of the lung injury, along with prolonged survival during exposure to lethal hyperoxia (Otterbein et al, 2003). All of these studies indicate that CO has anti-inflammatory effects.…”
Section: Inflammationmentioning
confidence: 78%